Trio obtainment through polypyrrole insertions in argentum/graphitic carbon nitride for accelerating super-capacitive energy parameters. (1st December 2022) - Arora, Rajat; Nehra, S.P.; Lata, Suman
Abstract: The Ag/g-C3 N4 @ppy (APN) nanocomposites were synthesized via in-situ polymerization. These synthesized composites were characterized through FT-Infra-Red spectroscopy, XRD, BET, UV and TGA. The morphological studies of the NCs were executed through FESEM and TEM techniques. The super-capacitive parameters of the differently ratioed samples were determined and noted that, 0.9 APN implies an optimized and best composition among all the other samples of the series, and it liberated the highest specific capacitance that is 602.2 F/g at 1 A/g current density and good capacitive retention as 95.23 % even over 10, 000 loops of charging and discharging. The NCs showed an excellent electrical energy accumulation than that of Ag/g-C3 N4 (ACN) as well as compared to that of pure g-C3 N4 . Highlights: Synthesis of Ag/g-C3 N4 @ppy or APN nanocomposites in-situ polymerization method 0.9 APN exhibits excellent specific capacitance of 602.2 F/g at scan rate 10 mV/s. The incredible cyclic stability of 95.23 % even after 10, 000 cycles Electrochemical parameters obtained via CV and GCD accord well. Three electrode as well as two electrode systems were studied with good results.